2022
DOI: 10.3390/ijerph19158992
|View full text |Cite
|
Sign up to set email alerts
|

Is Silver Diamine Fluoride Effective in Arresting Enamel Caries? A Randomized Clinical Trial

Abstract: Background: There is limited information on the effectiveness of 38% silver diamine fluoride (SDF) in managing enamel caries. Objective: This study aimed to compare effectiveness of 38% SDF and 5% Sodium fluoride (NaF) varnish in arresting enamel caries in young children when applied semiannually over 18 months. Methods: A randomized controlled trial was conducted on children aged 1–3 years who had at least one active carious surface. They were allocated into two groups: Group 1 (38% SDF) and Group 2 (5% NaF v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
6
2
1
Order By: Relevance
“…This agrees with Duangthip et al [11] who reported a small and non-significant difference between 30% SDF and 5% NaF in arresting ICDAS 3 or 4 lesions. Our findings disagree with Phonghanyudh et al [12] who reported that 38% SDF had significantly higher arrest rate of ICDAS 3 enamel lesions than NaF after 6 months. However, Phonghanyudh et al applied NaF varnish on affected lesions only unlike the present study where NaF varnish was applied to all teeth with greater area available to act as fluoride reservoir and continuously release fluoride than when applied on affected lesions only [46].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This agrees with Duangthip et al [11] who reported a small and non-significant difference between 30% SDF and 5% NaF in arresting ICDAS 3 or 4 lesions. Our findings disagree with Phonghanyudh et al [12] who reported that 38% SDF had significantly higher arrest rate of ICDAS 3 enamel lesions than NaF after 6 months. However, Phonghanyudh et al applied NaF varnish on affected lesions only unlike the present study where NaF varnish was applied to all teeth with greater area available to act as fluoride reservoir and continuously release fluoride than when applied on affected lesions only [46].…”
Section: Discussioncontrasting
confidence: 99%
“…It seems that the caregivers’ main concern was to stop caries progression regardless of the esthetics. These findings agree with previous studies [ 12 , 15 , 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In early enamel lesions, both fluoride varnish and SDF have been suggested as treatment strategies, especially in young children, due to their ease of application and safety [ 3 , 12 , 16 , 17 ]. The effect of SDF compared to NaF varnish on enamel remineralization was previously investigated [ 12 , 18 ]. Yet, up to our knowledge, our study is the first to compare the effect of SDF and fluoride varnishes containing calcium-phosphate on WSLs in primary teeth.…”
Section: Discussionmentioning
confidence: 99%